A Study on the Foreign Direct Investment in Thailand - Kunsabfueng, Wanna (KDI School, 2001)
Foreign direct investment (FDI) is one of the driving forces binding countries into closer economic interdependence. FDI flows have grown rapidly in recent years associated with the deeper liberalization of national and international investment regimes. Foreign direct investment—the acts of private businesses investing capital in a foreign country in order to produce goods or services—has contributed to a dense tissue of cross-country economic relations that, called “global economic interdependence”. Flows of foreign investment have increased dramatically in recent years. Between 1985 and 1997, they grew from around US$60 billion to US$400 billion, substantially faster than growth of international trade
Thesis(Master) --KDI School:Master of Public Policy,2001